Localization of the site of recombination in formation of the Lepore Boston globin gene. - Baird, M (1981)
The site of crossover between the delta- and beta-globin gene sequences resulting in Lepore Boston globin gene formation has been localized at the DNA Level. Probes specific for detecting the intervening sequences (IVS) of the delta- and beta-globin genes were used to map the origin of cellular DNA fragments of a patient homozygous for hemoglobin Lepore Boston. Restriction endonuclease analysis and hybridization of this DNA to IVS specific probes show that most, if not all, of the large intervening sequences (IVS 2) in Lepore DNA are derived from the beta-globin gene IVS 2. In addition, the crossover occurs in a region of DNA in which the delta- and beta-genes have almost complete nucleotide homology, and might be expected to pair most tightly during meiosis.